Quality in Early Childhood Education and Care through Leadership and Organizational Learning Organizational and Professional Development - Hansen, Line Skov.; Ringsmose, Charlotte (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book provides insights in to how high quality learning environments in Early Childhood Education and Care (ECEC) develop, and how competent systems can support this. It builds on the knowledge that quality early environments shape the wellbeing and development of the child, and explores how communities of professional practice that support quality development are built. Acknowledging that the conditions for providing high quality pedagogical work depend not only on the individual teacher, but also on collaboration and organizational and professional development. The book draws on a range of theoretical frameworks and research that underline competent systems rather than individualized learning as a path to improve workforce quality and professionalization in the field of ECEC.
Part 1. Systemness as a Starting Point for Leadership and Organi-zational and Professional Learning in Early Childhood Education and Care -- Chapter 1. In search of Pedagogical Heroes: What Makes Practitioners Im-prove their Pedagogical Practice? (Jan Peeters) -- Chapter 2. Conceptualizing Improvement Work through System-wide Coherence (Thomas Nordahl) -- Chapter 3. Building Professional Capital for High-quality Early Childhood Education and Care (Line Skov Hansen).-Part 2. Leadership, Organizational, and Professional Learning in Early Childhood Education and Care: Approaches, Experiences, and Results -- Chapter 4. Implementing Improvements in Early Childhood Education and Care Centers: From Individual Capacity to Organizational Learning (Charlotte Ringsmose) -- Chapter 5. Use of Data and Research-based Knowledge in Early Childhood Education and Care (Line Skov Hansen) -- Chapter 6. From Professionals in Context to Context with Professionals: Quality Improvements in Early Childhood Education and Care through Professional Learning Communities (Bent B. Andresen) -- Chapter 7. Increasing the Quality of Early Childhood Education and Care through Organizational Development (Anja Overgaard) -- Chapter 8. Professional and Organizational Development of Quality in Early Childhood Education and Care through Action Learning (Julie Borup Jensen).-Part 3. The Big Picture: Overviews and Insights on Leadership and Organizational and Professional Learning in Early Childhood Education and Care -- Chapter 9. What Do We Know about Professional Learning in Early Years Education? Findings From a Systematic Review (Sue Rogers) -- Chapter 10. Leadership in Professional Learning Communities: A Review of Literature (Kate Thornton) -- Chapter 11. Facilitating Cultures of Reflection through Professional Development for Sustainable Advancement in ECEC: Insights from a Series of Initiatives in Denmark (Bente Jensen) -- Chapter 12. Reconceptualizing Pedagogical Leadership for Quality in Early Childhood Education: From Individual Dispositions to Systemic Creativity (Joce Nuttall). .
Keywords: Early childhood education; Professional education; Vocational education; Teaching; Education and state; Early Childhood Education; Professional and Vocational Education; Pedagogy; Educational Policy and Politics